Interpretation of Minimum Age Limit for Regional Head and Vice Regional Head Candidates: Supreme Court Decision Number 23P/HUM/2024 Vs. Constitutional Court Decision Number 70/PUU-XXII/2024 - Selly Dayanti; Yoni Agus Setyono (Faculty of Law, Universitas Pekalongan, 2025)
Regarding the provisions on the minimum age limit for candidates for regional heads and deputy heads, has been regulated in Law Number 10 of 2016 concerning Elections. In the latest development, there are decisions of the Supreme Court and the Constitutional Court which further interpret this minimum age limit. The House of Representatives wanted to revise the Regional Election Law, and the revision plan carried out by the House of Representatives intended to use the SC’s decision as a reference in determining the minimum age limit for candidates for regional heads and deputy heads. The plan has caused controversy because the CC’s decision should have been used as a reference. This article uses a normative legal writing method with a statutory approach, as well as a case approach based on the SC’s decision Number 23P/HUM/2024 and the CC’s decision Number 70/PUU-XXII/2024. This article aims to analyze the interpretation of the minimum age limit based on the decisions of the two institutions, examine the legal force of the two decisions and the implications of the exclusion of the CC’s Decision on democracy and the constitution. This paper finds that legal products tested by the CC have a higher position in the hierarchy of legislation, and the CC's decision is final and binding, so in interpreting the minimum age limit for regional head and deputy regional head candidates, must refer to the CC's decision. If the House of Representatives ignores the CC's decision, it can have a negative impact on the constitution and democracy.